RETURNS TO EDUCATION AND WAGE DISTRIBUTION IN INDONESIA: A COMPARISON ACROSS GENDER GROUPS - Kadir Kadir; Weni Lidya Sukma (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
Abstract. This study is aimed to estimate the returns to education in Indonesia not only at the mean but also across the whole distribution by implementing quantile regression techniques and doing a comparison between gender groups. It also relates the estimation results to the two channels through which education affects the wages inequality, i.e., between-and within-educational-levels earning differentials. We found that education has a positive and significant impact on wage distribution implying that increasing the level of education could shift the wages distribution to the right. In general, the estimates of the returns to education for the female is higher than male. For each gender group, our study also confirms the presence of both the between-groups wages inequality associated with the difference in educational levels among individuals and the within-groups wages inequality caused by the difference in ability among individuals in the same level of education. Our findings suggest that promoting the same level of education for all, particularly tertiary education, could bring down the wages inequality although at the same time the inequality may still exist due to the difference in unobserved characteristic among individuals at the same level of education.